Memaksimalkan Nilai Pendidikan Islam dan Komunikasi dalam Upaya Mensukseskan Perekonomian Di Era 4.0 - Heru Cahyono (Etos : Jurnal Pengabdian Masyarakat, 2020)
The purpose of the implementation of this research is to determine the maximum value of Islamic Education and Communication in Efforts to Succeed the Economy in the Era of 4.0 in Parungjaya Village. because basically the economy is an important factor in people's lives. Both in meeting individual needs and society in general. The progress of a society can be seen from the ability of Islamic education, communication and economy. The higher the economic level of the community, the more prosperous the community's life is. This research uses a qualitative approach through case studies. Data obtained through in-depth interviews, observation, and documentation. The data analysis steps include data reduction, data presentation, and verification. The data sources needed to collect and process in this study are primary data and secondary data. Primary data is the parties who are used as research informants. This type of data includes information and information about the condition of the community in Parungjaya Village. And secondary data, namely various books containing public policy theory, theory of public policy implementation, as well as various documents and writings on the condition of the Parung Jaya village community as well as other data relevant to the needs and objectives of the study. Parungjaya Village itself, education has been very good, it can be seen from the awareness of the community who are aware of the importance of education. However, public interest in higher education is still lacking because they prefer to work. As well as religious activities that are already running actively in every block every week. However, from these activities the residents still lack enthusiasm to participate. Likewise, pottery is one of the superior products. Although in modern times like today, more sophisticated and modern tools have begun to erode. Like utensils made of clay etc. What is very unfortunate for them at this time is the lack of the next generation of pottery craftsmen. Based on the research results obtained, the author of Parung Jaya Village has implemented a comprehensive socialization and motivation strategy. Abstrak Tujuan pelaksanaan penelitian ini adalah untuk mengetahui maksimalnya Nilai Pendidikan Islam Dan Komunikasi Dalam Upaya Mensukseskan Perekonomian Di Era 4.0 Di Desa Parungjaya. karena pada dasarnya ekonomi merupakan faktor penting dalam kehidupan masyarakat. Baik dalam pemenuhan kebutuhan individu maupun masyarakat secara umum. Kemajuan suatu masyarakat dapat dilihat dari kemampuan pendidikan islam, komunikasi dan ekonomi. Semakin tinggi tingkat ekonomi masyarakat semakin sejahtera kehidupan masyarakatnya. Penelitian ini menggunakan pendekatan kualitatif melalui studi kasus. Data diperoleh melalui wawancara mendalam, observasi, dan dokumentasi. Adapun langkah-langkah analisis data meliputi reduksi data, penyajian data, dan verifikasi. sumber data yang diperlukan untuk menghimpun dan diolah dalam penelitian ini adalah data primer dan data sekunder. Data primer yaitu para pihak yang dijadikan informan penelitian. Jenis data ini meliputi informasi dan keterangan mengenai keadaan masyarakat di desa parungjaya. Dan data sekunder yaitu berbagai buku yang berisi teori kebijakan publik, teori implementasi kebijakan publik, serta berbagai dokumen dan tulisan mengenai keadan masyarakat desa parung jaya dan juga data lainnya yang relevan dengan kebutuhan dan tujuan penelitian. Desa Parungjaya sendiri, pendidikan sudah sangat baik, terlihat dari kesadaran masyarakat yang sadar akan pentingnya pendidikan, Namun minat masyarakat terhadap pendidikan perguruan tinggi masih kurang karena lebih memilih untuk bekerja. Serta kegiatan keagamaan sudah berjalan aktif di setiap blok setiap pekan. Namun dari kegiatan-kegiatan tersebut masih kurangnya antusias warga untuk turut serta. Begitu juga dengan gerabah merupakan salah satu produk unggulan. Meskipun pada jaman modern seperti saat ini, mulai tergerus oleh alat- alat yang lebih canggih dan modern. Seperti halnya perkakas yang terbuat dari tnah liat dll. Yang sangat disayangkan oleh mereka saat ini adalah kurangnya generasi penerus pengrajin gerabah. Berdasarkan hasil penelitian yang diperoleh, penulis Desa Parung Jaya sudah menjalankan strategi sosialisi dan motivasi secara menyeluruh.